INFRASTRUCTURE OF DISTANCE WORK IN CONDITIONS OF CORONACRISIS - ZUB, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The concept of remote work is considered in the article, its characteristic features are investigated. Situational, planned, fixed types and two types (type of employment and type of self-employment) of remote work are determined. The author's definition of the terms "remote work" and "remote worker" is given. Emphasis is placed on the main problems of infrastructural support of remote work in the regions of Ukraine. The author emphasizes that the need for flexibility of remote work infrastructure, its foresight, innovation, adaptability to challenges, ability to mobilize the region's resource potential in overcoming crises should motivate domestic officials to reconsider regional development priorities. The expediency of building a viable infrastructure for remote work in Ukraine, which could operate on different fronts simultaneously and synchronously, is substantiated.The author's interpretation of the concept of "remote work infrastructure" as a system of regulatory, organizational, technical and informational components that help transform remote workers into active agents who are able to independently or with the help of the employer to create autonomous remote jobs anywhere and perform functional tasks , minimize costs, increase motivation and productivity. A conceptual model of the system of remote work infrastructure at the regional level is proposed.It is proved that the determinant of the functioning of effective remote work infrastructure is increasing the attractiveness of remote work in the regions of Ukraine, ensuring the continuity of enterprises, firms, institutions and organizations, increasing new decent remote jobs, expanding remote employment, dynamic living standards and improving health. creating equal employment opportunities for all citizens; reduction of costs of labor market participants, increase of labor productivity; reduction of regional asymmetries, strengthening of interregional cooperation, increase of digitalization and transformation of economic changes in the regions of Ukraine.
Keywords: remote work; remote worker; types and types of remote work; infrastructure of remote work; conceptual model of system of infrastructure of remote work at regional level